The Relationship Between Duration of Hemodialysis and Level of Depression Among Hemodialysis Patients in Kupang City - Suriana Desty Maltus; Teguh Dwi Nugroho; Audrey Gracelia Riwu; Arley Sadra Telussa (Asosiasi Dosen Muda Indonesia, 2026)
Hemodialysis is a long-term renal replacement therapy that can affect patients’ daily functioning and psychological well-being. Depression is common in this population and may reduce quality of life and treatment adherence. However, evidence on whether hemodialysis duration is associated with depression remains inconsistent, and local multi-center data from Kupang City are limited. Objective: To analyze the relationship between duration of hemodialysis and depression level among hemodialysis patients in Kupang City. Methods: A quantitative cross-sectional study was conducted in July–August 2025 at three hemodialysis centers in Kupang City (RSUD W.Z. Johanes, RS Siloam, and RSUP Ben Mboi). Using purposive sampling, 163 respondents were recruited from a population of 365 routine hemodialysis patients. Depression was assessed using the Beck Depression Inventory-II (BDI-II). Hemodialysis duration was obtained from medical records and categorized as <12 months, 12–24 months, and >24 months. Data were analyzed descriptively and tested using the Chi-square test. Findings: Most respondents were not depressed (60.7%), while 39.3% had mild to severe depression. The largest proportion had undergone hemodialysis for >24 months (35.6%). There was no statistically significant association between hemodialysis duration and depression level (p = 0.434). Implications: Depression among hemodialysis patients appears to be influenced by factors beyond treatment duration, supporting the need for routine depression screening and psychosocial support integrated into hemodialysis care. Originality: This multi-center study provides local evidence from three hospitals in Kupang City using a standardized instrument (BDI-II), helping clarify inconsistent prior findings and reinforcing a multifactorial view of depression in hemodialysis patients.